2019
DOI: 10.1521/pedi_2018_32_334
|View full text |Cite
|
Sign up to set email alerts
|

Differential Change of Borderline Personality Disorder Traits During Dialectical Behavior Therapy for Adolescents

Abstract: Despite the expansion of treatment options for adults with borderline personality disorder (BPD), research on treatment options for adolescent BPD is scarce. The aim of this study was to investigate the impact of dialectical behavior therapy for adolescents (DBT-A) on the individual trait level as primary outcome; and the frequency of suicide attempts and nonsuicidal self-injury, self-reported BPD core pathology, and general psychopathology as secondary outcomes. Seventy-two adolescents (aged 12.17 years) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 44 publications
3
21
0
8
Order By: Relevance
“…An issue when studying personality in psychiatric clinical samples is how to deal with the question of state versus trait, since the feared state effect on reports of traits ought to be stronger in psychiatric clinical samples. It has previously been shown that both personality traits [36] and personality disorders [37] are inflated during phases of psychiatric illness and normalize after treatment. This study deals with the state versus trait issue by dividing participants according to current mental status based on CPRS-S-A scores.…”
Section: Discussionmentioning
confidence: 99%
“…An issue when studying personality in psychiatric clinical samples is how to deal with the question of state versus trait, since the feared state effect on reports of traits ought to be stronger in psychiatric clinical samples. It has previously been shown that both personality traits [36] and personality disorders [37] are inflated during phases of psychiatric illness and normalize after treatment. This study deals with the state versus trait issue by dividing participants according to current mental status based on CPRS-S-A scores.…”
Section: Discussionmentioning
confidence: 99%
“…An integrated treatment approach that involves collaboration between services is needed to improve treatment access and engagement for this particular group. Third, mixed-effects linear regression analyses did not nd a group difference in clinical improvement over time, indicting that both groups bene ted from the received treatment that included elements from cognitive behavioral therapy and dialectical behavioral therapy (66,67). However, due to the short follow-up period and the substantial amount of missing data in the current study, this nding has to be considered as preliminary.…”
Section: Discussionmentioning
confidence: 96%
“…The outcome part of the study addresses the following questions: In adolescents suffering from BPP, does an intensive outpatient treatment with the new approach AIT lead to an outcome that is comparable (non-inferior) to an intensive treatment with DBT-A? The non-inferiority design was chosen since DBT-A already has been established as an effective treatment [ 15 , 34 , 35 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%